Efek Pemberian Ekstrak Etanol Daun Leilem (Clerodendrum minahasae) terhadap Kadar Kreatinin, Asam Urat dan Ureum pada Tikus Putih (Rattus novergicus) - Rumondor, Rolef; Komalig, Muhammad Rino; Kamaluddin, Kamaluddin (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2019)
The progress of science in the field of medicine is currently very rapid along with technological advances, but the use of traditional medicines is increasingly popular. This is due to the low side effects caused by traditional medicines, practical use, easy to obtain and affordable prices. North Sulawesi is one area that has so many types of plants, including leilem plants (Clerodendrum minahassae) of the genus Clerodendrum. Leilem plant is an endemic plant in North Sulawesi which is often consumed by vegetables as a vegetable and is usually added to meat processing. This study aims to determine the effect of ethanol extracts of leilem leaves on the description of urea, uric acid and creatinine values ​​in etylen glycol induced white rats. The study design, the treatment group was divided into 5 groups. The control group (P0), the ethylene glycol group (P1), the rockgin treatment group (P2), the ethanol extract group of leilem leaves at a dose of 150 mg / kgBB (P3), and the ethanol extract group of leilem leaves at a dose of 300 mg / kgBB (P4). The results showed that the ethanol extract of leilem leaves 150 mg / kgBB and 300 mg / kgBB could reduce the levels of ureum, creatinine and uric acid in rats with ethylene glycol treatment. Ethanol extract of leilem leaves 150 mg / kgBB was better in reducing levels of urea, creatinine and uric acid in rats compared with a dose of 300 mg / kgBB (p <0.05)